A coordinated relay protection strategy of distribution network based on fault current limiting. (November 2022) - Zeng, Qingpeng; Zhang, Zhifeng; Xu, Mingming; Zhu, Jin; Chi, Teng; Wei, Tongzhen
Abstract: In order to solve the problem of difficult coordination of traditional overcurrent relay protection caused by short supply radius and little difference of fault current along urban distribution network, a coordinated relay protection strategy based on economical fault current limiter (FCL) is proposed. The FCL device is configured at the export of the main transformer, by using quick fault identification method, setting different protection current value and relay protection delay time, once the fault occurs, the FCL can quickly limit the fault current first then cooperate with the circuit break and switches on the feeder line to achieved the coordinated relay protection. Combining with faults occurring at different locations along the feeder line, the composition and basic working principle of the FCL are discussed, the theory of fast fault identification method and the setting method of the coordinated relay protection parameters are emphatically discussed. The simulation results show that the proposed current limiting coordinated relay protection strategy can effectively reduce the short-circuit current level and bus voltage drop during the fault handle processing, thus reduce the damage to the distribution system and influence range of the fault, greatly improve the selectivity of the relay protection finally.